Use of Literary Texts in Cross-cultural Education - Senkāne, Olga; Laganovska, Karīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The objective of this study is to propose a new methodological solution for mastering classical literary works, emphasizing the role of a literary text in cross-cultural education. For this purpose, different genres of the German traditional and modernist prose have been selected: H. Hesse's novel “The Glass Bead Game” and W. Borchert’s short story “On This Tuesday”. The study seeks to demonstrate the efficiency of combining phenomenological approach and semiotics in identifying the notions of other cultures and analysis of their functionality in literary works by means of applying this method in audiences of various specialty students. A particular object of the study is cross-cultural education – the process of mastering systematized individual knowledge and skills and forming attitudes, which is related to the interaction between different cultures. starpkultūru izglītība, semiotika, kultūras zīme, fenomens.